2017
DOI: 10.1016/j.jnucmat.2017.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Nanoindentation study of the combined effects of crystallography, heat treatment and exposure to high-flux deuterium plasma in tungsten

Abstract: This document is intended for publication in the open literature. It is made available on the clear understanding that it may not be further circulated and extracts or references may not be published prior to publication of the original when applicable, or without the consent of the Publications Officer, EUROfusion Programme Management Unit,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…This study reveals highly relevant new details of the interaction between deuterium and dislocations in tungsten. The observed strain hardening agrees with previous studies [77,94,102] on tungsten. Moreover, we were also able to capture the pinning effect by deuterium-induced vacancies, which has only been experimentally reported for aluminum as measured with an environmental transmission electron microscope [41].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study reveals highly relevant new details of the interaction between deuterium and dislocations in tungsten. The observed strain hardening agrees with previous studies [77,94,102] on tungsten. Moreover, we were also able to capture the pinning effect by deuterium-induced vacancies, which has only been experimentally reported for aluminum as measured with an environmental transmission electron microscope [41].…”
Section: Discussionsupporting
confidence: 92%
“…It is worth mentioning that the pop-ins observed here are distinct from those described in [76][77][78]. In those studies, the effect of hydrogen plasma exposure on the pop-in response in tungsten was investigated, whereby it was concluded that the hydrogen plasma exposure reduces the pop-in probability.…”
Section: Stepwise Tds and Nanoindentationmentioning
confidence: 68%
“…In terms of mechanical properties, retained deuterium can bring about reduced pop-in load and increase in hardness (maximum increase of 0.5 GPa) as observed by nanoindentation of tungsten exposed to deuterium plasma at 443 K, with incident ion energy of 35 eV and accumulated fluence of 8.1 × 10 25 ions/m 2 [15]. Similar observations of increased hardness were made by Terentyev et al [115] and Zayachuk et al [116] in tungsten exposed to deuterium plasma. Overall, observations from past studies clearly indicate that despite the fast diffusion of hydrogen isotopes at fusion relevant temperatures, a significant percentage of the injected ions will be trapped by irradiation defects.…”
Section: The Effect Of Hydrogen On the Plasma-facing Componentsupporting
confidence: 70%
“…Substantially, irradiation hardening in plasma-exposed materials has been generally ascribed to dislocations (loops) [6], bubbles or cavities [5,41] and D penetration [42], etc. However, the specific roles played by distinct damage defects on irradiation hardening are rarely reported in previous literatures.…”
Section: Discussionmentioning
confidence: 99%
“…In their following study, the mechanical properties of deuterium (D) plasma-exposed tungsten was tested by the Berkovich nano-indentation, and the surface hardening was attributed to the D deposition measured by the corresponding nuclear reaction analysis (NRA) profile [5]. Zayachuk et al [6] also suggested that the irradiation hardening after high flux D plasma exposure originated from the trapping of diffusing D atoms by dislocations in both deformed and recrystallized tungsten. In the meanwhile, H blisters, acting as the primary surface modification at the service condition [7] are also expected to be strongly connected with the changes of mechanical properties after H plasma exposure.…”
Section: Introductionmentioning
confidence: 99%